The Development of the Major Characters in the Drama “Les Miserables” - Belevska, Ivet Rosenova; Sumaryana Putra, I Komang (Humanis, 2017)
This study entitled “The Development of the Major Characters in the Drama Les Miserables” was aimed to identify the methods of characterization used in introducing the major characters, and also analyzing the intrinsic and extrinsic motivations that the major characters develop. The data for this study was taken from the drama script and 25th Anniversary stage performance of the drama “Les Miserables”. In collecting the data this study used library research and the data itself was analyzed qualitatively. Finally, the method of characterization of the major characters as well as the characters’ motivations are explained. Reaske’s theory of characterization in drama is used to determine the major characters’ methods of characterization. For analyzing the motivations of the characters’, the theory by Ryan and Deci is applied. From the discussion of characterization and human motivations it can be concluded that the major characters have various methods of characterization, such as character in action, dialogue between characters, asides and soliloquies, the appearance of a character, and hidden narration. However, the one that was used twice on two separate characters was dialogue between characters. The characters develop in accordance to their motivations and the majority of the character’s motivations are concluded to be intrinsic.
Keywords: drama, major characters, characterization, intrinsic and extrinsic motivation